Does the use of a diving mask adapted for non-invasive ventilation in hypoxemic acute respiratory failure in individuals with and without COVID-19 increase the PaO2/FiO2 ratio? A randomized clinical trial - Sônia Elvira dos Santos Marinho; Dulciane Nunes Paiva; Guacyra Magalhães Pires Bezerra; Thayse Neves dos Santos Silva; Cláudia Regina Oliveira de Paiva Lima; Maria Cristina Falcão Raposo; Patrícia Érika de Melo Marinho (Monaldi Archives for Chest Disease, 2023)
Non-invasive ventilation (NIV) can be used in acute hypoxemic respiratory failure (AHRF); however, verifying the best interface for its use needs to be evaluated in the COVID-19 pandemic scenario. To evaluate the behavior of the PaO2/FiO2 ratio in patients with AHRF with and without COVID-19 undergoing NIV with the conventional orofacial mask and the adapted diving mask. This is a randomized clinical trial in which patients were allocated into four groups: Group 1: COVID-19 + adapted mask (n=12); Group 2: COVID-19 + conventional orofacial mask (n=12); Group 3: non-COVID + adapted mask (n= 2); and Group 4: non-COVID + conventional orofacial mask (n=12]. The PaO2/FiO2 ratio was obtained 1, 24 and 48 h after starting NIV and the success of NIV was evaluated. This study followed the norms of the CONSORT Statement and registered in the Brazilian Registry of Clinical Trials, under registration RBR – 7xmbgsz. Both the adapted diving mask and the conventional orofacial mask increased the PaO2/FiO2 ratio. The interfaces differed in terms of the PaO2/FiO2 ratio in the first hour [309.66 (11.48) and 275.71 (11.48), respectively] (p=0.042) and 48 h [365.81 (16.85) and 308.79 (18.86), respectively] (p=0.021). NIV success was 91.7% in groups 1, 2 and 3, and 83.3% in Group 4. No adverse effects related to interfaces or NIV were observed. NIV through the conventional orofacial mask interfaces and the adapted diving mask was effective in improving the PaO2/FiO2 ratio, however, the adapted mask presented a better PaO2/FiO2 ratio during use. There was no significant difference between interfaces regarding NIV failure.